PEDAGOGICAL CONTENT KNOWLEDGE MAHASISWA PENDIDIKAN FISIKA UNIVERSITAS JAMBI PADA PRAKTIK LAPANGAN PERSEKOLAHAN - M.Hidayat; Dani, Rahma; Lestari, Neneng (Program Studi Pendidikan Fisika FKIP Universitas Jambi, 2020)
This study aims to describe the ability of pedagogical content knowledge students of Physics Education Jambi University who take School Field Practices (SFP). This research was a survey research. The population of this research was 85 students who are taking SFP. The number of samples used was 20% of the population. Data were collected using a questionnaire. Data were analyzed descriptively. The results showed that the students' pedagogical content knowledge ability was in a good category. Aspects of pedagogical content knowledge consist of subject matter knowledge, instruction representation and strategies, instructional objective and context and knowledge of student understanding.